2021
DOI: 10.3390/nano12010145
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and Quantitative Analysis of Tumor Cell Invasion Using Au Clusters

Abstract: Tumor invasion/metastasis is still the major cause of death in cancer patients. Membrane type-1 matrix metalloproteinase (MT1-MMP) is directly related to tumor invasion/metastasis. To accurately and quickly distinguish the risk of invasion/metastasis of primary tumor cells, it is urgent to develop a simple and precise quantitative method to distinguish the expression level of MT1-MMP. In this work, we have constructed red fluorescent Au clusters with peroxidase-like properties that could specifically bind to M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…Cell motility is an important indicator for evaluating cell viability. 37 , 38 Wound‐healing studies showed that the motility of HepG2 cells was not affected by different PCLA scaffolds treatment, further proving that these scaffolds were not toxic to cells (Figure 4F,G ). As expected, coated scaffolds did not exhibit cytotoxicity to A549 cells (Figure S6 ).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Cell motility is an important indicator for evaluating cell viability. 37 , 38 Wound‐healing studies showed that the motility of HepG2 cells was not affected by different PCLA scaffolds treatment, further proving that these scaffolds were not toxic to cells (Figure 4F,G ). As expected, coated scaffolds did not exhibit cytotoxicity to A549 cells (Figure S6 ).…”
Section: Resultsmentioning
confidence: 79%
“…As depicted in Figure 4E, after treatment with different coating PCLA scaffolds, the count of HepG2 cells did not decrease, indicating that these scaffolds had good biosafety for HepG2 cells. Cell motility is an important indicator for evaluating cell viability 37,38 . Wound‐healing studies showed that the motility of HepG2 cells was not affected by different PCLA scaffolds treatment, further proving that these scaffolds were not toxic to cells (Figure 4F,G).…”
Section: Resultsmentioning
confidence: 80%
“…Over the preceding decades, heightened attention has been directed towards Au clusters due to their extensive utility in * Author to whom any correspondence should be addressed. catalytic applications [4][5][6], nanoelectronic devices [7] and biomedical science [8,9]. Preliminary investigations of Au clusters have unveiled that the most stable Au clusters are typified by organized closely packed arrangements, such as the octahedral face-centered cubic (fcc) structure [10], twin fcc structure [11], twin hexagonal closed packed (hcp) structure [12], truncated icosahedral structure [13] and truncated decahedral structure [14].…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al have successfully synthesized chiral Au NCs assemblies with strong circular dichroism (CD) by using atomically precise Au NCs to fabricate ordered assembled structures with emerging optical activity [ 46 ]. By understanding the mechanism of assembly structure, noble metal NCs would be excellent candidates for assembled building blocks [ 47 , 48 ]. Due to their thermodynamic stability, the number of constituent atoms of various types can be easily synthesized in large quantities and could assemble heterogeneous structure at the atomic level [ 49 ].…”
Section: Introductionmentioning
confidence: 99%